Thermoelastic transition kinetics of a gamma irradiated CuZnAl shape memory alloy - Ozgen, Soner; Tatar, Cengiz (Korean Inst Metals Materials, 2012)
Many types of shape memory alloys have been used in nuclear reactors and aerospace applications where they are exposed to high levels of various kinds of radiation. The effect of gamma irradiation on the transformation kinetics of thermoelastic transformations in a shape memory CuZnAl alloy was investigated by differential scanning calorimetry (DSC) with heating/cooling rates of 10, 20, 30 and 40 A degrees C/min. Irradiation doses of 10, 20, 30 and 40 kGy were applied to the samples of the alloy. Changes in Gibbs free energies, entropies and elastic energies were calculated. Reverse transition temperatures A (s) and A (f) systematically decreased with increasing doses, although forward transition temperatures M (s) and M (f) underwent a minimum value at a dose of 20 kGy. Hysteresis in the transition temperatures changed as an inverse parabolic function of the irradiation dose. The activation energies of transformations were calculated by using Kissinger and Osawa methods.
Keywords: shape memory alloys; homogenization; thermodynamic properties; thermal analysis; irradiation effect